2015
DOI: 10.1074/jbc.m114.611111
|View full text |Cite|
|
Sign up to set email alerts
|

Short Term Exposure of Beta Cells to Low Concentrations of Interleukin-1β Improves Insulin Secretion through Focal Adhesion and Actin Remodeling and Regulation of Gene Expression

Abstract: Background: Molecular mechanisms involved in beneficial effects of IL-1␤ on beta cell function are poorly understood. Results: Short exposure of beta cells to low concentrations of IL-1␤ enhanced stimulated insulin secretion through focal adhesion, actin remodeling, and transcription. Conclusion: The beneficial effects of IL-1␤ occur at multiple molecular levels. Significance: IL-1␤ has opposing effects on beta cells depending on time of exposure and concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 68 publications
2
35
0
Order By: Relevance
“…Consistent with previous reports (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), acute exposure to IL-1β (10 ng/ml) enhanced glucose-stimulated insulin secretion from mouse ( Figure 1A) and human ( Figure 1B) islets. IL-1β had no effect on islet insulin content and did not affect secretion at low glucose (data not shown).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with previous reports (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), acute exposure to IL-1β (10 ng/ml) enhanced glucose-stimulated insulin secretion from mouse ( Figure 1A) and human ( Figure 1B) islets. IL-1β had no effect on islet insulin content and did not affect secretion at low glucose (data not shown).…”
Section: Resultssupporting
confidence: 81%
“…One of several proposed mechanisms underlying the IL-1β-mediated potentiation of insulin secretion is an IL-1β-induced rise in [Ca 2+ ] i (32,38,39). While it is known that the insulinotropic effect of IL-1β requires Ca 2+ flux into the β cell (31,34), whether the stimulatory effects of IL-1β are due to an increase in [Ca 2+ ] i is still debated (29,30,32,34,38). To provide further insight into the mechanism of IL-1β-stimulated insulin release, Ca 2+ currents and [Ca 2+ ] i were measured following treatment with IL-1β.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although IL-1␤ has been implicated in ␤-cell destruction (42,43), it has been suggested that IL-1␤ itself is not sufficient to cause ␤-cell death and that low concentration or short term treatment with IL-1␤ may even have beneficial effects on ␤-cell function and survival (44,45), which is in alignment with the observed reduction in pro-apoptotic TXNIP expression. Interestingly, TXNIP has previously been shown to be involved in inflammasome activation and to thereby induce IL-1␤ production (46).…”
Section: Discussionsupporting
confidence: 57%
“…Whatever the source, the effects of cytokines on beta cell function and survival depend on several other factors, including, in particular, their concentrations and combinations. For example, low levels of IL-1β promote beta cell proliferation and improve insulin secretion [41,42]; furthermore, when human beta cell preparations were cultured for 48 or 72 h with or without IL-1β, TNFα or IFNγ, none of these single cytokines was toxic to the beta cells [43].…”
Section: Islet Expression Of Cytokines and Chemokines In Type 2 Diabetesmentioning
confidence: 99%